Historical evolution of the teaching-learning process of Physics in pre-university education (REDEL. Revista Granmense de Desarrollo Local, 2025)
The historical study of the educational process is an indispensable way to understand the evolution of pedagogical practices and the transformations that have determined its current state. This article addresses the historical evolution of the teaching-learning process of Physics and the development of scientific culture among pre-university students. To this end, the regularities of each of the defined stages (four) were determined using their corresponding indicators. The central axis of analysis and reflection was the application of the historical-logical method and the qualitative research technique of content analysis. The study allowed for an in-depth examination of the transformations that occurred in each stage, in correspondence with the particular characteristics of pre-university students during the treatment of the content.
Keywords: content analysis; historical evolution; qualitative research; historical-logical method.